Pengaruh keberlanjutan pengadaan terhadap logistik balik dengan moderasi kebijakan pemerintah - Dewi Sabrina Eka Putri; Wahyuningsih Santosa; Ratna Darasih; Dorina Widodati (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2025)
This study aims to examine the effect of sustainable procurement on reverse logistics, with government policy as a moderating variable. The three dimensions of sustainable procurement tested are environmental, economic, and social. A quantitative approach was employed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method, involving 159 respondents from a toy manufacturing company in Indonesia. The analysis shows that only one of the six proposed hypotheses was statistically significant: the influence of economic sustainable procurement on reverse logistics. The environmental and social dimensions had no significant effect, and government policy did not moderate any of the relationships. These results emphasize the importance of economic efficiency in procurement as a key factor in reverse logistics, while environmental and social aspects, along with government policy, require further development to enhance sustainability outcomes